Carbon nanotube fiber mats for microbial fuel cell electrodes. (November 2017) - Delord, Brigitte; Neri, Wilfrid; Bertaux, Karen; Derre, Alain; Ly, Isabelle; Mano, Nicolas; Poulin, Philippe
Graphical abstract: New electrodes with large porosity and nanostructuration made of woven carbon nanotube fibers for high current density microbial fuel cells. Highlights: New carbon nanotube based textile fiber electrode for microbial fuel cells. Electrode with 3D hierarchical porosity to facilitate biofilm formation. Superior properties demonstrated with Geobacter sulfurreducens bacteria. Potential application in future microbial fuel cell technology. Abstract: Novel carbon nanotube based electrodes of microbial fuel cells (MFC) have been developed. MFC is a promising technology for the wastewater treatment and the production of electrical energy from redox reactions of natural substrates. Performances of such bio-electrochemical systems depend critically on the structure and properties of the electrodes. The presently developed materials are made by weaving fibers solely comprised of carbon nanotubes. They exhibit a large scale porosity controlled by the weaving process. This porosity allows an easy colonization by electroactive bacteria. In addition, the fibers display a nanostructuration that promotes excellent growth and adhesion of the bacteria at the surface of the electrodes. This unique combination of large scale porosity and nanostructuration allows the present electrodes to perform better than carbon reference. When used as anode in a bioelectrochemical reactor in presence of Geobacter sulfurreducens bacteria, the present electrodes show a maximal current density of about 7.5 mA/cm 2 .